N-octanoyl dopamine attenuates the development of transplant vasculopathy in rat aortic allografts via smooth muscle cell protective mechanisms - Wedel, Johannes; Yard, Benito A. (Transplantation, 2016)
Background: Transplant vasculopathy (TV) is a major cause for late graft loss after cardiac transplantation. Endothelial damage and T cell infiltration play a pivotal role in the development of TV. Because N-octanoyl dopamine (NOD) inhibits vascular inflammation and suppresses T cell activation in vitro, we here tested the hypothesis that NOD treatment ameliorates TV. Methods: Aortic grafts were orthotopically transplanted in the Dark Agouti to Brown Norway strain combination. Recipient rats were treated with NOD or vehicle administered via osmotic minipumps. Histology and quantitative polymerase chain reaction (qPCR) were performed on nontransplanted aortas and grafts explanted 2 and 4 weeks after transplantation to assess the degree of TV, inflammation, apoptosis, and number of (proliferating) α smooth muscle actin (αSMA)+ neointimal cells. In vitro analyses of human aortic smooth muscle cells were performed to test the effect of NOD on proliferation (WST-1 assay), cell cycle (flow cytometry and qPCR), and cytokine-induced apoptosis (flow cytometry). Results: Allografts from vehicle-treated recipients developed neointimal lesions predominantly consisting of αSMA-expressing cells. NOD treatment significantly reduced neointima formation and neointimal αSMA+ cells. In situ, smooth muscle cell proliferation (Ki67) was not influenced by NOD. Macrophage (CD68), T (CD3), and Natural Killer (ANK61) cell infiltration as well as intragraft TNFα and IFNγ mRNA expression were similar in both groups. Medial apoptosis (cleaved caspase-3) was significantly reduced by NOD. In vitro, NOD inhibited proliferation of human aortic smooth muscle cells by causing a G1-arrest and protected from TNFα-induced apoptosis. Conclusions: This study identified NOD as potential treatment modality to attenuate TV. Our data clearly support a vasculoprotective effect of NOD by reducing smooth muscle cell proliferation and inflammation-induced apoptosis.